모델 예측 제어 기법을 이용한 3-레벨 인버터로 구동되는 영구자석 동기 전동기의 토크 리플 저감 기법 - 노승완 (The Graduate School, Ajou University, 2014)
This paper proposes a model predictive control (MPC) method that applies the space vector modulation (SVM) technique to a permanent magnet synchronous motor (PMSM) driven by a three-level neutral-point-clamped (NPC) inverter. The MPC method selects the optimized voltage vector for the inverter control using the predictive modeling equation of the PMSM and cost function. However, since the conventional MPC method uses the limited voltage vector to control the inverter, large torque ripple is generated. The proposed algorithm performs the torque ripple reduction by synthesizing voltage vectors of various magnitudes, selecting optimal voltage vectors through the cost function implementation, and switching with space vector modulation (SVM). The proposed control method is validated through the simulation and experimental results.
학위논문(석사)--아주대학교 일반대학원 :전자공학과,2014. 8
Keywords: 모델예측제어기법; 3레벨인버터; 토크리플저감기법